Legal protections against unfair competition in e-commerce: Analysis of Indonesian and Thailand framework adequacy - Lu Sudirman; Nipon Sohheng; Agustianto; Shenti Agustini; Nurlaily (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: Unfair competition threatens economic growth and is harder to detect in the digital era. For Indonesia and Thailand, growing digital economies depend on fair online marketplaces, yet these platforms face risks like price manipulation and visibility bias. Addressing these issues is crucial to unlocking their global trade potential. Purpose/Study Objectives: The purpose of this research is to analyze the normative potentials and challenges in enforcing antitrust laws in Indonesian and Thai online marketplaces, particularly in addressing antitrust challenges that are unique to the digital environment. Design/Methodology/Approach: This research utilizes normative legal research method and a comparative legal approach to examine the frameworks for protecting against unfair competition in online marketplaces in Indonesia and Thailand. Findings: Findings of this study highlight that the existing antitrust laws in Indonesia and Thailand are not equipped to address the unique challenges of digital markets, such as algorithm-driven price fixing, product visibility manipulation, and data monopoly. The study proposes a legal framework model focusing on enhancing algorithmic transparency, ensuring search neutrality, establishing robust market monitoring, and integrating data governance with antitrust measures. This model aims to bolster fair competition and consumer protection, positioning both nations to leverage their digital economy potentials effectively. Paper Type: Research Article